Reliable role of public relations in social innovation processes - Torres Valdés, Rosa María (2021)
Social innovation is recognized by multilateral organizations as a way to cope creatively and collaboratively with social demands that are not satisfied, neither from the public nor from the private. This challenge requires management reliable relationship between actors with diverse and sometimes conflicting interests. In this sense, the social function of public relations (PR) can provide an important service to prevent resistance to social changes that involve innovation processes. The literature consulted shows that theorizations on social innovation, recommend cultivating relational capital and theories and models PR provide methods and techniques to reliably achieve said capital. A documentary investigation and a case study based on the participatory-action-research that is the basis of a theoretical prot-model ofintervention of reliable PR in social innovation processes. It’s a study exploratory and descriptive with a sequential methodology.